2010
DOI: 10.1074/jbc.m109.094763
|View full text |Cite
|
Sign up to set email alerts
|

The XBP-Bax1 Helicase-Nuclease Complex Unwinds and Cleaves DNA

Abstract: XPB helicase is an integral part of transcription factor TFIIH, required for both transcription initiation and nucleotide excision repair (NER). Along with the XPD helicase, XPB plays a crucial but only partly understood role in defining and extending the DNA repair bubble around lesions in NER. Archaea encode clear homologues of XPB and XPD, and structural studies of these proteins have yielded key insights relevant to the eukaryal system. Here we show that archaeal XPB functions with a structure-specific nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Furthermore, the ThM motif of XPB intrudes between the two ssDNA tails like a wedge with the 3′-overhang extending through the channel formed by the HD2/ThM of XPB (Figures 1D and 2A and B ) and the 5′-overhang extending into the space between two N-terminal β-hairpins of Bax1 ΔC (Figures 1D and 2A ). These observations are consistent with the 3′–5′ helicase polarity of archaeal XPB ( 7 ) (moving along the 3′-overhang strand toward the fork junction) and the nuclease activity of Bax1 on the DNA substrate containing a 5′-overhang ( 33 ) in vitro . Neither XPB nor Bax1 ΔC interacts with the remaining nucleotides of the two ssDNA tails further away from the fork, leading to poor electron density for this portion of the DNA.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, the ThM motif of XPB intrudes between the two ssDNA tails like a wedge with the 3′-overhang extending through the channel formed by the HD2/ThM of XPB (Figures 1D and 2A and B ) and the 5′-overhang extending into the space between two N-terminal β-hairpins of Bax1 ΔC (Figures 1D and 2A ). These observations are consistent with the 3′–5′ helicase polarity of archaeal XPB ( 7 ) (moving along the 3′-overhang strand toward the fork junction) and the nuclease activity of Bax1 on the DNA substrate containing a 5′-overhang ( 33 ) in vitro . Neither XPB nor Bax1 ΔC interacts with the remaining nucleotides of the two ssDNA tails further away from the fork, leading to poor electron density for this portion of the DNA.…”
Section: Resultssupporting
confidence: 82%
“…Our structure assigns XPB residues 165–300 to a DRD-like domain that connects the NTD to the RecA-like domain ( Figure 3A , Figure 3—figure supplement 1A ), the deletion of which is lethal in yeast ( Warfield et al, 2016 ). The DRD is a DNA-binding domain found in DNA repair enzymes and chromatin remodelers ( Mason et al, 2014 ; Obmolova et al, 2000 ) and has been implicated in DNA damage recognition in archaeal XPB ( Fan et al, 2006 ; Rouillon and White, 2010 ). Our 3.7 Å-resolution map of TFIIH reveals that in eukaryotic XPB, one β-strand of the DRD of archaeal XPB is replaced by an insertion of approximately 70 residues that exhibits relatively low sequence conservation ( Figure 3E , Figure 3—figure supplement 1B ) and shifts the domain boundaries of the human XPB DRD-like domain with respect to previous sequence alignments ( Fan et al, 2006 ; Oksenych et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, GFP tagged mutants were defective in recruitment to sites of UV damage in CHO cells, suggesting that recruitment of XPB to damage is an active process requiring ATP hydrolysis coupled with structural stabilization of XPB on DNA by the ThM domain and RED motif [108]. In vitro experiments using mutant Sulfolobus solfataricus XPB (SsoXPB) proteins, found that the RED motif is involved but not essential for SsoXPB function while both the ThM and DRD domains were essential for XPB function [109], confirming the importance of these accessory domains and motifs for XPB function.…”
Section: Introductionmentioning
confidence: 99%